Influence of Miscibility on Poly(ethylene oxide) Crystallization from Disordered Melts of Block Copolymers with Lithium and Magnesium Counterions - Thelen, Jacob L; Chen, X. Chelsea; Inceoglu, Sebnem; Balsara, Nitash P (Macromolecules, 2017)
Crystallization within block copolymers is a subject of considerable interest; however, little is understood about how the presence of an ion-containing block, such as poly[(styrene-4-sulfonyltrifluoromethylsulfonyl)imide (P[(STFSI)]), influences the crystallization behavior of single-ion conducting block copolymers derived from poly(ethylene oxide)-b-poly[(styrene-4-sulfonyltrifluoromethylsulfonyl)imide (PEO–P[(STFSI)]). In this study, we report on the crystallization behavior of PEO in a matched-set library of lithiated (PEO–P[(STFSI)Li]) and magnesiated (PEO–P[(STFSI)2Mg]) single-ion conducting block copolymers that are disordered in the melt. Structural and thermal analysis of semicrystalline samples prepared by quenching amorphous melts reveals that total PEO crystallinity is independent of cation identity. Furthermore, crystallization induces the formation of lamellar nanostructures regardless of the counterion present. However, the quality of the PEO crystallites and concomitant nanostructures appears to be strongly influenced by counterion identity; magnesiated samples demonstrate more disorder at both the crystalline and nanostructural level. By monitoring PEO crystallization with in situ small and wide-angle X-ray scattering, we show that PEO crystallizes from a homogeneous melt within PEO–P[(STFSI)Li] but is hindered by the presence of disordered concentration fluctuations within the magnesiated samples. Thus, counterion identity influences PEO crystallization by controlling the miscibility of the polymer blocks within the crystallizing melt.